Instrumentation Organizational and Economic Support of Labor Motivation of Employees - Mamycheva, Diana I.; Melnichuk, Aleksandr V.; Taranova, Irina V.; Chernykh, Anatoly I.; Gadzhieva, Elena Yu.; Ratiev, Vitaly V. (International Review of Management and Marketing, 2016)
The problem of motivation of employees is a top priority in a number of organizational and economic problems of the modern enterprise. The willingness of the staff to do their work is a key factor in the success of the enterprise. Each manager is interested in the fact that a worker taken separately and the team as a whole worked more effectively. Mechanical forced to work cannot give a high positive. The path to the formation and development of effective management of the enterprise worker is through the understanding of its work motivation. Establish and develop an effective system of forms and methods of employee motivation can only know that he is motivated by what is the motive for his activity, what motives lie at the heart of its actions. Then must understand how there are certain motives, in what way the latter can be operated, how the motivation of employees. To increase the effectiveness of work is possible through knowledge of the structure of motives and needs of employees; specific measures for loyal perception of the company’s management and promotion of the significant results; improving the quality of the information structure and decision-making structures by optimizing the communication. Keywords: efficiency of production, work, labor economics JEL Classifications: D6; E2